Proceedings of XXIX International Symposium on Lattice Field Theory — PoS(Lattice 2011) 2012
DOI: 10.22323/1.139.0157
|View full text |Cite
|
Sign up to set email alerts
|

Excited state contamination in nucleon structure calculations

Abstract: Among the sources of systematic error in nucleon structure calculations is contamination from unwanted excited states. In order to measure this systematic error, we vary the operator insertion time and source-sink separation independently. We compute observables for three source-sink separations between 0.93 fm and 1.39 fm using clover-improved Wilson fermions and pion masses as low as 150 MeV. We explore the use of a two-state model fit to subtract off the contribution from excited states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 11 publications
(12 reference statements)
1
20
0
Order By: Relevance
“…The most straightforward strategy to address this problem is to include the first excitation into the fit ansatz for R(t, t s ) (see ref. [26]) or to investigate larger values of t and t s [27].…”
Section: R(t T S )mentioning
confidence: 99%
“…The most straightforward strategy to address this problem is to include the first excitation into the fit ansatz for R(t, t s ) (see ref. [26]) or to investigate larger values of t and t s [27].…”
Section: R(t T S )mentioning
confidence: 99%
“…In general, excited states can cause significant systematic errors in three-point functions and hadron matrix elements [23]. We compute our form factor values as averages of three central points in the plateaus.…”
mentioning
confidence: 99%
“…This yields improved asymptotic behaviour [3,4], with the leading excited-state contaminants decaying as Te −∆E min T . Other approaches such as various forms of multistate fits [5][6][7][8][9][10][11] and the use of a variational basis of interpolating operators [12][13][14][15] have also been explored. Besides excited states, important systematics include the following:…”
Section: Arxiv:14124637v1 [Hep-lat] 15 Dec 2014mentioning
confidence: 99%
“…However, this discrepancy persisted as pion masses were reduced. Studies of contributions from excited states have found large effects [5,10,15,18], and that by reducing them and using relatively light pion masses, much of the gap between lattice calculations and experiment could be closed. This is displayed in Fig.…”
Section: Electromagnetic Form Factorsmentioning
confidence: 99%